2022
DOI: 10.3389/fpls.2022.964656
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the genetic basis of bioactive metabolites and fruit quality traits in blueberries (Vaccinium corymbosum L.)

Abstract: Blueberry is well-recognized as a healthy fruit with functionality derived largely from anthocyanin and chlorogenic acid. Despite their importance, no study to date has evaluated the genetic basis of these bioactives in blueberries and their relationship with fruit quality traits. Hence, to fill this gap, a mapping population including 196 F1 individuals was phenotyped for anthocyanin and chlorogenic acid concentration and fruit quality traits (titratable acidity, pH, and total soluble solids) over 3 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 66 publications
3
14
0
Order By: Relevance
“…The present study identifies a strong QTL for the tested phenolic acids, and its overlap with the QTL region identified by Mengist et al [ 46 ] lends credence to our finding. However, the lack of independent populations in which markers could be tested means that any genetic selection, such as in a breeding program, would require using an individual or parent from the BNJ16-4 population as the donor.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The present study identifies a strong QTL for the tested phenolic acids, and its overlap with the QTL region identified by Mengist et al [ 46 ] lends credence to our finding. However, the lack of independent populations in which markers could be tested means that any genetic selection, such as in a breeding program, would require using an individual or parent from the BNJ16-4 population as the donor.…”
Section: Discussionsupporting
confidence: 91%
“…Comparing the results of trait mapping presented here with the previous findings of Mengist et al [ 46 ] showcases the mapping power of the interspecific population. While Mengist et al [ 46 ] used a population of 196 individuals and found QTL for CGA with LOD scores of 5.9–6.9, the present study used a comparable number of individuals and identified QTL for CGA with LOD scores of ~16.0. This difference is likely partially explained by the larger difference between the parents in the present study.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations